Transformasi Pembelajaran dengan Coding: Membekali Pendidik MI Manba’ul Huda dalam Meningkatkan Literasi Digital Siswa - Sulastri, Asri; Anisa, Ana; Ibrahim, Tatang (Lembaga Yasin AlSys, 2024)
In the era of globalization which is marked by rapid technological development, education has undergone a significant transformation so it is considered important to innovate learning with coding through the ScracthJr application which aims to increase digital literacy in students and the introduction of coding as a learning method at MI Manba'ul Huda. This study uses a qualitative descriptive approach, with data collection through observation and in-depth interviews with teachers, madrasah heads, and students' parents. The results of the study show that the application of coding not only improves students' digital skills but also stimulates critical and logical thinking skills. A total of 57.1% stated that this coding was appropriate to be applied in learning, but as many as 64.3% stated that this coding could improve digital literacy in students while 35.7% expressed doubts. This is because there are difficulties from educators to master the coding, but this is a demand for educators to have more innovative competencies.